Synthesis and full-spectrum-responsive photocatalytic activity from UV/Vis to near-infrared region of S-O decorated YMnO3 nanoparticles for photocatalytic degradation of ibuprofen - Feng, Zixia (Frontiers in Chemistry, 2024)
The oxalic acid complexation method and sulfuric acid heat treatment method were used to synthesize the YMnO3 (YMO) and YMO-SO4 2-(YMO-SO) photocatalysts. The YMO-SO photocatalyst maintained the crystal structure of YMO, but the particle size increased slightly and the optical band gap decreased significantly.The YMO-SO photocatalyst demonstrates a wide range of light absorption capabilities, covering ultraviolet, visible and near-infrared light. The photocatalytic activity of YMO-SO was investigated with ibuprofen as the target pollutant. The YMO-SO photocatalyst exhibits high ultraviolet (UV), visible and near-infrared photocatalytic activity. Experiments with different environmental parameters confirmed that the best catalyst content was 1 g/L, the best drug concentration was 75 mg/L and the best pH value was 7. The capture experiment, free radical detection experiment and photocatalytic mechanism analysis confirmed that the main active species of YMO-SO photocatalyst were hole and superoxide free radical.